Sources of inflation and the effects of balanced budgets and inflation targeting in developing economies - Guilherme Klein Martins; Peter Skott (University of Massachusetts, Department of Economics, 2020)
This paper presents a model of inflation in developing economies and makes uses of it to evaluate macroeconomic policy in those countries. We see cross-sectoral interactions between demand and supply side forces as central and show that the standard macroeconomic policy recommendations of inflation targeting and balanced budgets (i) increase volatility by amplifying external shocks and (ii) can lead to premature deindustrialization. The analysis applies to economies with marked underemployment, a central feature of developing and emerging countries. The recent Brazilian experience is used to illustrate the argument.
Keywords: E63; O23; O14; 330; inflation targeting; Dutch disease; overvaluation; commodities boom; Washington consensus